LEARNING MANAGEMENT AT SMP ASSALAM ISLAMIC SCHOOL JEUNIEB, BIREUEN REGENCY - Sardiati, Sardiati; Marsithah, Iis; Iskandar, Iskandar (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to describe the management of learning at SMP Assalam Islamic School Jeunieb using the POAC approach (Planning, Organizing, Actuating, Controlling). The research employed a descriptive qualitative method, with data collected through interviews, observation, and documentation. The research subjects included the principal, vice principal for curriculum, and teachers. The results showed that in the planning stage, the school designed the learning process collaboratively and integratively between the national curriculum and the Islamic curriculum based on the dayah system. The principal, vice principal, and teachers were involved in developing integrative lesson plans (RPP), adjusting the morning tahfiz schedule, and identifying the necessary teaching components. In the organizing stage, the school established a clear organizational structure, assigned tasks according to teacher competencies, and ensured regular coordination. The management of learning facilities and infrastructure was carried out systematically and carefully by the education staff. The implementation stage combined modern and traditional methods such as lectures, discussions, sorogan, bandongan, and memorization. Teachers actively integrated general subject content with Islamic values to create meaningful and religious learning experiences. The supervision stage was carried out hierarchically, both internally by the principal and vice principal, and externally by supervisors from the education office and the dayah institution. Supervision included classroom observations, evaluation of teaching documents, and assessments of students’ academic and spiritual development. The findings indicate that the POAC approach can be effectively applied to manage integrated learning that combines two curricula. The study also resulted in a model of integrative learning management based on Islamic values in the context of Islamic boarding schools.